2014
DOI: 10.1155/2014/157645
|View full text |Cite
|
Sign up to set email alerts
|

Observation Study on the Size Distribution of Sand Dust Aerosol Particles over Yinchuan, China

Abstract: The Yinchuan area, which lies in the eastern part of Northwest China, is one of the main transportation paths and origins of sand dust in China. In order to investigate the aerosol number size distribution and its temporal-spatial evolution over this area, direct solar radiation data taken from September 2012 to October 2013 by a sun photometer CE-318 located at Beifang University of Nationalities (106°29′E, 38°13′N) were analyzed. The particle number size distributions were retrieved from the aerosol optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…4a), are selected to examine the relationship between the local ASI TS and PM 2.5 concentrations. All those cities have been suffering heavy aerosol pollution reported by previous studies (Huang et al 2011;Sun et al 2013;Han et al 2014;Mao et al 2014;Wang et al 2014;Gui et al 2016;J. Li et al 2017;.…”
Section: B the Daily Variations Of Asi Ts In Ncmentioning
confidence: 83%
“…4a), are selected to examine the relationship between the local ASI TS and PM 2.5 concentrations. All those cities have been suffering heavy aerosol pollution reported by previous studies (Huang et al 2011;Sun et al 2013;Han et al 2014;Mao et al 2014;Wang et al 2014;Gui et al 2016;J. Li et al 2017;.…”
Section: B the Daily Variations Of Asi Ts In Ncmentioning
confidence: 83%
“…Helan. The geographic details of Yinchuan and the surrounding regions were introduced and can be seen in Mao et al (2014). A sun photometer CE-318 was installed on teaching building No.…”
Section: The Experiments and Results Analysismentioning
confidence: 99%
“…In addition, the particle volume size distributions have a peak in~4.7 mm during dust events around the cities around the desert regions in western and central Inner Mongolia (Zhuang et al, 2001;Park and Kim, 2006;Zhou et al, 2005;Liu et al, 2005), while Guo et al (2012) found 20% of the largest particle size distribution function located in 1.2e2.2 mm for PM 10 in Hotan around Taklimakan Desert. Mao et al (2014) indicated particle size distribution in spring was obviously larger than that in other seasons due to frequent occurrence of dust events and particle number size distributions had two obvious peaks at the particle radius of 0.6 mm and 1.4 mm during dust events over Yinchuan around Gobi desert. Yabuki et al (2005) found dust storms or blowing dust occurred not only in spring, but also in summer and autumn, though floating dust occurred mainly in March and April at Aksu around Taklimakan desert.…”
Section: Effects Of Dust On Downstream Urban Air Qualitymentioning
confidence: 95%